Low-Dose Apatinib Optimizes Tumor Microenvironment and Potentiates Antitumor Effect of PD-1/PD-L1 Blockade in Lung Cancer - Zhao, Sha; Ren, Shengxiang; Jiang, Tao; Zhu, Bo; Li, Xuefei; Zhao, Chao; Jia, Yijun; Shi, Jinpeng; Zhang, Limin; Liu, Xiaozhen; Qiao, Meng; Chen, Xiaoxia; et al. (Cancer immunology research, 2019)
The lack of response to treatment in most lung cancer patients suggests the value of broadening the benefit of anti-PD-1/PD-L1 monotherapy. Judicious dosing of antiangiogenic agents such as apatinib (VEGFR2-TKI) can modulate the tumor immunosuppressive microenvironment, which contributes to resistance to anti-PD-1/PD-L1 treatment. We therefore hypothesized that inhibiting angiogenesis could enhance the therapeutic efficacy of PD-1/PD-L1 blockade. Here, using a syngeneic lung cancer mouse model, we demonstrated that low-dose apatinib alleviated hypoxia, increased infiltration of CD8 T cells, reduced recruitment of tumor-associated macrophages in tumor and decreased TGFβ amounts in both tumor and serum. Combining low-dose apatinib with anti-PD-L1 significantly retarded tumor growth, reduced the number of metastases, and prolonged survival in mouse models. Anticancer activity was evident after coadministration of low-dose apatinib and anti-PD-1 in a small cohort of patients with pretreated advanced non-small cell lung cancer. Overall, our work shows the rationale for the treatment of lung cancer with a combination of PD-1/PD-L1 blockade and low-dose apatinib.